Pengaruh Content Marketing dan Influencer Marketing terhadap Keputusan Pembelian melalui Purchase Intention sebagai Variabel Intervening pada Produk Skintific: Studi pada Generasi Z di Kabupaten Purworejo - Eka Yuni Astuti; Intan Puspitasari; Dedi Runanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The beauty industry in Indonesia, especially the skincare sector, continues to show significant growth. To win the market, entrepreneurs strive to produce the best quality products and determine the right marketing strategy. Skintific used a content marketing and influencer marketing strategy with a TikTok Ads campaign, and engaged popular influencers such as Cut Rizki, Tasya Farasya, and Nicholas Saputra. This strategy succeeded in increasing brand exposure, but also caused negative reactions due to the high frequency of advertisements which were considered annoying by some users. Therefore, this study aims to analyze the effect of Content Marketing and Influencer Marketing on Purchasing Decisions through Purchase Intention as an Intervening Variable. This research design uses quantitative methods with a sample size of 150. Data collection using a questionnaire with a Likert scale. This research was conducted in Purworejo Regency using quantitative methods and Structural Equation Modeling (SEM) analysis through SmartPLS. The results showed that Content Marketing has a positive and significant effect on Purchasing Decisions, Influencer Marketing has a positive and significant effect on Purchasing Decisions, Content marketing has a positive and significant effect on purchase intention. Influencer marketing has a positive and significant effect on purchase intention, Purchase intention has a positive and significant effect on purchasing decisions, Purchase intention mediates the effect of content marketing on purchasing decisions, and Purchase intention mediates the influence of influencers on purchasing decisions.